Value of Edema-like Marrow Signal Intensity in Diagnosis of Joint Pain: Radiologists' Perspective - Kim, Dong Kyun; Lee, Sheen-Woo (Seminars in Musculoskeletal Radiology, 2023)
Musculoskeletal pain is a significant contributor to disability. The mechanism and target of the treatment should be optimized by imaging, but currently no accepted gold standard exists to image pain. In addition to end-organ pathology, other mediators also contribute to nociception, such as angiogenesis, axonal extension, immunologic modulation, and central sensitization. Recent research indicates that local inflammation is a significant contributor to pain in the extremities; therefore, we focus here on edema-like marrow signal intensity (ELMSI). We examine both the relevance of ELMSI for pain and novel imaging techniques.
Keywords: pain; pain imaging; bone marrow edema; edema-like marrow signal intensity